Design of a Minimized Complementary Illusion Cloak with Arbitrary Position - Yan Shi; Lin Zhang; Wei Tang; Long Li; Chang-Hong Liang (International Journal of Antennas and Propagation)
This paper has developed a complementary illusion cloak to hide the objects with arbitrary shapes and sizes. In the proposed cloak, a complementary cloak is first introduced by using the trapezoid coordinate transformation. Then an illusion device in terms of another trapezoid coordinate transformation is designed to cloak the object. With two coordinate transformations, the complementary illusion cloak device can be arbitrarily placed to hide the target object, and the sizes of the antiobject used to cloak the object are obviously compressed. Numerical results including target objects with different shapes are given to verify correctness and effectiveness of the proposed cloak.